2021
DOI: 10.1007/s12325-021-01904-6
|View full text |Cite
|
Sign up to set email alerts
|

Roxadustat for the Maintenance Treatment of Anemia in Patients with End-Stage Kidney Disease on Stable Dialysis: A European Phase 3, Randomized, Open-Label, Active-Controlled Study (PYRENEES)

Abstract: Introduction: Roxadustat is an orally administered hypoxia-inducible factor prolyl hydroxylase inhibitor being developed for the treatment of anemia of chronic kidney disease (CKD). This European, phase 3, randomized, open-label, active-controlled study investigated efficacy and safety of roxadustat in patients with endstage kidney disease on dialysis for at least 4 months. Methods: Patients were randomized to switch from an erythropoiesis-stimulating agent (ESA) (epoetin alfa or darbepoetin alfa) to roxadusta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 26 publications
2
67
2
3
Order By: Relevance
“…The hemoglobin response rate in another clinical trial was defined as an increase from the baseline of at least 1.0 g per deciliter in the hemoglobin level by Chen et al [ 16 ]. In PYRENEES (Roxadustat in the Treatment of Anemia in End-Stage Renal Disease Patients on Stable Dialysis), a Phase 3 controlled study, where 836 patients were randomized, the non-inferiority of Roxadustat versus ESA was declared for the change in Hb levels from baseline to the average of weeks 28-36 since the lower bound of the 95% CI was higher than 0.75 g/dL [ 17 ]. In our study, we choose a change of 0.75 g/dl as the hemoglobin response rate.…”
Section: Methodsmentioning
confidence: 99%
“…The hemoglobin response rate in another clinical trial was defined as an increase from the baseline of at least 1.0 g per deciliter in the hemoglobin level by Chen et al [ 16 ]. In PYRENEES (Roxadustat in the Treatment of Anemia in End-Stage Renal Disease Patients on Stable Dialysis), a Phase 3 controlled study, where 836 patients were randomized, the non-inferiority of Roxadustat versus ESA was declared for the change in Hb levels from baseline to the average of weeks 28-36 since the lower bound of the 95% CI was higher than 0.75 g/dL [ 17 ]. In our study, we choose a change of 0.75 g/dl as the hemoglobin response rate.…”
Section: Methodsmentioning
confidence: 99%
“…In another phase 3 trial, this time in 305 DD patients, roxadustat was statistically noninferior (difference, 0.2 ± 1.2 g/dl; 95% CI: −0.02 to 0.5) in maintaining hemoglobin compared to epoetin alfa [5 ▪▪ ]. More recently, the PYRENEES study in 836 dialysis patients [17 ▪ ], and the DOLOMITES study in 616 nondialysis patients [18 ▪ ] have confirmed the efficacy of roxadustat in maintaining hemoglobin levels in a target range of 10–12 g/dl up to 104 weeks of treatment.…”
Section: Effect On Hemoglobin and Anemiamentioning
confidence: 96%
“…Roxadustat (FG‐4592) is a hypoxia‐inducible factor prolyl hydroxylase inhibitor (HIF‐PHI), which is a new class of oral agents for the treatment of CKD anaemia 7 . In phase 3 clinical trials, roxadustat proved effective in correcting anaemia in non‐dialysis CKD patients or maintaining haemoglobin (Hb) after switching from ESA in dialysis patients 8–13 . Roxadustat has been marketed in China for CKD patients and covered by medical insurance for 3 years.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…7 In phase 3 clinical trials, roxadustat proved effective in correcting anaemia in non-dialysis CKD patients or maintaining haemoglobin (Hb) after switching from ESA in dialysis patients. [8][9][10][11][12][13] Roxadustat has been marketed in China for CKD patients and covered by medical insurance for 3 years. Because HIF-PHIs can regulate the expression of erythropoietin and iron metabolism genes, 14 roxadustat may be effective in correcting ESA-hyporesponsive anaemia.…”
mentioning
confidence: 99%